2013
DOI: 10.7322/jhgd.50387
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepnessand Cardiometabolic Risk Factors in Children and Teenagers With Overweight

Abstract: Introdução: atualmente, é observada tendência exacerbada para sonolência diurna excessivaem crianças e adolescentes com excesso de peso. A obesidade e os distúrbios do sono, têmefeito conjunto nas doenças cardiovasculares e no diabetes mellitus. Objetivo: avaliar aprevalência de sonolência diurna excessiva e sua associação com fatores de riscocardiometabólicos. Método: estudo de corte transversal realizado em serviço público, referênciaem atendimento a crianças e adolescentes com excesso de peso no período de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(37 reference statements)
0
4
0
1
Order By: Relevance
“…Poor sleep quality was more prevalent among the study adolescents. This condition may affect wake quality to a variable degree, especially in this age group, since they go to bed late in their biological configuration and tend to wake up late, which is not possible during the school year, resulting in excessive daytime sleepiness 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality was more prevalent among the study adolescents. This condition may affect wake quality to a variable degree, especially in this age group, since they go to bed late in their biological configuration and tend to wake up late, which is not possible during the school year, resulting in excessive daytime sleepiness 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these aspects allow us to speculate that adolescents with a higher fat percentage are less likely to present sleep benefits after a short-term strength-training program. Corroborating this hypothesis, previous studies have shown that the frequency of daytime sleepiness is higher among obese individuals 35 . Furthermore, values of body mass index are associated with impaired daytime sleepiness in obese adolescents 36 .…”
Section: Discussionmentioning
confidence: 68%
“…Contudo, 49,1% (n=26) das crianças e adolescentes investigados, apresentaram valores de HOMA-RI superior a 2,5 unidades. No estudo de Sena et al 24 a RI foi confirmada em 36,8% de crianças e adolescentes com excesso de peso. Entender a obesidade como um processo inflamatório é primordial para a compreensão da possibilidade do desenvolvimento da resistência à insulina precocemente.…”
Section: Discussionunclassified